DIGITAL TRANSFORMATION AND STATE-OWNED BANK'S PERFORMANCE: THE MODERATING EFFECT OF RISK PREFERENCE - Ahmad Sutanto; Wivan Febriansyah; Wita Juwita Ermawati (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
This study examines the impact of digital transformation on the financial performance of Indonesian state-owned banks, using risk preference as a moderating variable. The study utilizes data from the annual financial reports of Indonesian state-owned banks from 2019 to 2023. Digital transformation is measured through text mining of annual reports, bank performance is primarily indicated by Net Interest Margin (NIM), and risk preference is assessed using the Z-score. Given the presence of autocorrelation in the fixed effects model, the Generalized Method of Moments (GMM) is employed. The results reveal that digital transformation does not directly affect bank performance. However, this relationship is significantly moderated by the banks' risk preferences. Banks with higher risk preference tend to leverage digital transformation more effectively, resulting in increased profitability and higher risks. Conversely, banks with lower risk preferences adopt digital technologies more cautiously, achieving steadier but potentially lower gains. These findings offer valuable insights for policymakers and bank managers in the Indonesian banking sector, emphasizing balancing technological advancements with risk management to maintain financial stability. This study highlights the crucial role of digital transformation in enhancing bank performance when aligned with risk management strategies and contributes to the understanding of the complex relationship between digital transformation, risk preference, and bank performance in emerging economies, particularly in the context of state-owned banks.